Posthumous America Literary Reinventions of America at the End of the Eighteenth Century - Hoffmann, Benjamin (Penn State University Press, 2018)
Posthumous America examines the literary idealization of a lost American past. It investigates the reasons why, for a group of French writers of the 18th and 19th centuries, America was never more potent as a driving ideal than in its loss. For example, Hoffmann examines the paradoxical American paradise depicted in Crèvecœur's Lettres d'un cultivateur américain (1784); the "uchronotopia" of Lezay-Marnésia's Lettres écrites des rives de l'Ohio (1800)-the imaginary perfect society set in America and based on what France might have become without the Revolution; and the political and nationalistic motivations behind Chateaubriand's idealization of America in Voyage en Amérique (1827) and Mémoires d'outre-tombe (1850). From an historical perspective, Posthumous Americas works to determine when exactly these writers stopped transcribing what they actually observed in America and started giving imaginary accounts of their experiences.